Estudo experimental de vigas de concreto armado reforçadas à flexão com polímero reforçado com fibra de carbono - Vieira, Mylene de Melo (2014)
The reinforced concrete structures, when properly designed and performed, have prolonged its life. However, the lack of proper maintenance, acting loads greater than the design ones, pathological manifestations due to aggressive environment and accidents can impair the performance of the structure requiring the need for repair or structural strengthening. The technique of structural strengthening with application of carbon fiber reinforced polymer (CFRP), bonded externally to the reinforced concrete has advantages such as fast execution, which added to the characteristics of the composite as a high modulus of elasticity make wide its use. The aim of this study is to analyze through an experimental program the structural behavior of reinforced concrete beams strengthened in bending with CFRP. The methodology used was the production of three groups of five RC beams each one, with the same dimension of rectangular cross section, for bending test. The first group of beams was called VA. The second and third groups, called VB and VC and had different ratio of reinforcement. In each group of five beams, one beam was not strengthened (reference beam) and the remaining beams were strengthened with two, three, four and five layers of carbon fiber. The experimental results indicate the efficiency of strengthening, noting an increase in stiffness in all strengthened beams. The increase of load capacity was also observed in all groups of beams varying between 9,11% and 16,69%, 55,14% and 86,83%, 89,46% and 126,18%, of the beams of group VA, VB and VC, respectively in relation to the reference beam of each group. Of the carried through study was observed the excellent performance of strengthening in bending with carbon fiber especially in beams with the lowest ratios of reinforcement (group C), besides gathering a lot of information that can be useful for design criteria of the recovered and strengthened structures.